2021
DOI: 10.1159/000511909
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection for Crohn’s and Cancer: A Comparison of Disease-Specific Risk Factors and Outcomes

Abstract: <b><i>Background and Objectives:</i></b> The goal of this study was to compare disease-specific risk factors and 30-day outcomes between patients with Crohn’s disease (CD) and colon cancer (CC) undergoing right-sided surgical resection. <b><i>Methods:</i></b> The American College of Surgeons-National Surgical Quality Improvement Program (ACS-NSQIP<sup>®</sup>) was interrogated to extract all patients ≥18 years undergoing elective right-sided resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The rates of Midline vertical IH (7.9%) and Pfannenstiel IH (0%) in patients with Crohn's disease reported in our study are in line with the literature on right colectomy for colon cancer (Midline 2.2%-22.6%, Pfannenstiel 0-3.8%) [25][26][27][28][29][30][31][32][33][34]. Patients with in ammatory bowel disease have a higher incidence of IH and surgical complications than patients with colon cancer because of multiple surgeries, corticosteroids, malnutrition, smoking, and poor general status [9,19]. However, the IH rate in this cohort was lower than a recent study on patients with cancer reported by Widmar et al [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rates of Midline vertical IH (7.9%) and Pfannenstiel IH (0%) in patients with Crohn's disease reported in our study are in line with the literature on right colectomy for colon cancer (Midline 2.2%-22.6%, Pfannenstiel 0-3.8%) [25][26][27][28][29][30][31][32][33][34]. Patients with in ammatory bowel disease have a higher incidence of IH and surgical complications than patients with colon cancer because of multiple surgeries, corticosteroids, malnutrition, smoking, and poor general status [9,19]. However, the IH rate in this cohort was lower than a recent study on patients with cancer reported by Widmar et al [34].…”
Section: Discussionsupporting
confidence: 88%
“…Up to 30% of patients will have a repeat intestinal resection within 10 years [5]. Ileocolic resection is the most common surgical procedure for CD [1][2][3]6], and minimally invasive surgery (MIS) has improved postoperative outcomes in ileocolic resection for CD [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery (MIS) shares the same benefits as open approaches with enhanced recovery‚ making it the ideal approach for patients with CD. [9][10][11][12] Unfortunately, conversion rates for laparoscopic approaches remain high secondary to unique features of CD including multifocal disease, high rates of previous surgery, distorted anatomy, and the technical challenges associated with inflamed and friable tissues often observed with chronic immunosuppression and penetrating disease. [13][14][15][16][17][18] The advances of the robotic platform may decrease conversions and allow a more aggressive MIS approach to CD by facilitating complex lysis of adhesions and improved management of intraoperative bleeding associated with mesenteric division that often limits laparoscopic approaches.…”
Section: Medidas De Resultadomentioning
confidence: 99%
“…Mixing different baseline diseases might lead to inaccurate conclusions given important differences (immunosuppression, age, comorbidities). 15 Therefore, postoperative complication profiles, in particular, regarding infectious complications, are expected to be different depending on the underlying disease. Mixing open and laparoscopic approaches may also lead to false conclusions if confounders like the length of incision, surgical duration, or postoperative recovery are considered.…”
Section: Discussionmentioning
confidence: 99%